White Oyster Mushroom (Pleurotus ostreatus) As A Source of Food Fiber and Its Applications in Meat Processing - Audina Putri; Djoko Kisworo; Bulkaini Bulkaini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
White oyster mushrooms (Pleurotus ostreatus) can be used as fillers sausages mix because the physical properties of chewy like meat and high fiber content. The main raw material of sausages is meat, so that rejected layer chicken meat can be used even though it has low quality of the meat and less liked by the consumer, however, as a food ingredient it still has potential to improve the quality. Therefore, to improve the quality and preferences of the consumer, it is necessary to innovate processed into sausages with the addition of a fiber source, namely white oyster mushroom flour. This study aims to examine the use of white oyster mushroom as a source of dietary fiber in sausage processing. The research materials used were white oyster mushrooms, rejected laying hens and spices. The experiment was designed using a completely randomized design (CRD) with 4 treatments and 3 replications, which included: without the addition of white oyster mushroom flour P0 (0%), the addition of oyster mushroom flour at the level of P1 (5%), P2 (10%), P3 ( 15%). Data were analyzed based on analysis of variance using Statistical Analysis System (SASÃ¢â¬âSoftware). The results showed that the level of white oyster mushroom flour increased the organoleptic value of color, aroma and texture significantly (P<0.05). The addition of white oyster mushroom flour was also higly significant (P<0.01) in increasing the crude fiber content of sausages. It can be concluded that cooking loss was higher in line with the level of white oyster mushroom flour. But not on the value of water holding capacity. The higher the level of white oyster mushroom flour, the higher the crude fiber of the sausage. In general, the quality of sausages meets the Indonesian National Standard (SNI 3820 - 2015), interms of normal organoleptic value.